A Popular Approach, but Do They Work? A Systematic Review of Social Marketing Campaigns to Prevent Sexual Violence on College Campuses. (March 2023) - Lee, Chelsey; Bouchard, Jessica; Wong, Jennifer S.
College campuses continue to face high rates of sexual violence and social marketing campaigns have emerged as a common prevention strategy. However, there exists no summative research examining the effectiveness of this approach. A systematic search yielded 15 evaluations of eight unique prevention campaigns, which contributed to 38 individual outcome measures across four outcome categories (i.e., knowledge, attitudes, intentions/efficacy, and behavior). Summative results are mixed, but show promising campaign effects for increasing knowledge, modification of some attitudes toward sexual violence, intentions to participate, and actual participation in prevention activities. More evaluative research is needed for a comprehensive understanding of campaign effectiveness.